Analisis Tata Kelola Kebijakan Pajak Parkir Dan Retribusi Parkir Di Kota Malang (Universitas 17 Agustus 1945 Surabaya, 2023)
Malang City is one of the cities that has a highly reliable h population growth rate. Therefore, the city of Malang is inseparable from social problems due to overcrowding, one of which is parking problems. The rapid growth of parking must be accompanied by good governance. Issues such as a large number of idle spaces parking and causing high parking points in Malang City are not accompanied by increased parking fees and party taxes. This results in many illegal fees that the Malang City authority does not notice. The study's methodology is qualitative, where points of analysis use Grintheory, a grand theory where the success of policy implementation is fours based: ints, namely policy objectives, policy benefits, policy impacts, and program objectives. While the day, the technique of technique triangulation method. According to the findings of this study, parking management and parking fees in Malang City are managed by the Department of Transportation and the Regional Revenue Agency, where Regional Regulation Number 3 of 2015 serves as the foundation for parking management in Malang City, and the inhibiting factors for parking management in Malang City are parking attendants other than field coordinators who are not recorded by the Transportation Agency, resulting in budget leakage; and manpower.